2015
DOI: 10.9775/kvfd.2014.12769
|View full text |Cite
|
Sign up to set email alerts
|

Türkiye’de Sığırlardan İzole Edilen M. tuberculosis Suşlarının Spoligotiplendirmesi

Abstract: Although it is generally accepted that M.bovis leads to tuberculosis in cattle, there are statements given from the different regions of the world, referring to the fact that M. tuberculosis, which is known as the human tuberculosis agent, causes tuberculosis in cattle as well. The material of the study consisted of 13 M. tuberculosis isolates which were isolated and identified from the organ pieces of 95 cattle with the culture methods; these organ pieces had been taken from the cattle with granulomatous lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Tuzcu et al (20), in a report on M. bovis strains isolated from cattle slaughtered in Çukurova region, have found that 11 of the strains were M. bovis SIT 683 (SB0140), 4 of them were ST 685 (SB288), 7 were M. bovis subsp. caprae ST 647 (SB0418) while 2 strains' spoligotype pattern (220003777377600, 674077777777600) did not match any of the strains in the database.…”
Section: Discussionmentioning
confidence: 99%
“…Tuzcu et al (20), in a report on M. bovis strains isolated from cattle slaughtered in Çukurova region, have found that 11 of the strains were M. bovis SIT 683 (SB0140), 4 of them were ST 685 (SB288), 7 were M. bovis subsp. caprae ST 647 (SB0418) while 2 strains' spoligotype pattern (220003777377600, 674077777777600) did not match any of the strains in the database.…”
Section: Discussionmentioning
confidence: 99%
“…Spoligotyping was carried out according to the manufacturer's instructions (Spoligotyping Kit; Isogen LifeScience, Utrecht, The Netherlands) and described by Kamerbeek et al after DNA isolation from 42 M. bovis samples [22][23][24]. In order to obtain DNA from spoligotyping and MIRU-VNTR applied to all 42 M. bovis isolates, extraction was made from 7H9 broth medium and LJ medium by using a Mickle tissue disintegrator.…”
Section: Spoligotypingmentioning
confidence: 99%
“…Republic of China, Nigeria and Spain (6,7,8,9,10), and also, in India (11,12). In addition, in the district of Gandhinagar, Gujarat state, in western India, captive wild ruminants infected with MT have been reported (13).…”
Section: Introductionmentioning
confidence: 99%